Significance of philosophy in film as an important content analysis in film studies and criticism in Malaysia / Aidi Rahimi Hj. Ibrahim - Hj. Ibrahim, Aidi Rahimi (2006)
Most of the film reviews in Malaysia deal with 'fault-finding' rather than appearing as critical analysis of the film. Emphasis has been given on approaching film making commercially and as an entertainment; aim has been rather to making profit than to invoking philosophical issues and interpretation. Methodology Survey among film academicians and film practitioners in Malaysia concerning the knowledge and the substance of Philosophy in Film and their concern and point of views. Interviews are also conducted which are the primary data. Findings 1. Film as Seventh Art: (The Significance of Understanding Philosophy in Film) 2. Film as a Product of Occident: (The Significance of Evaluating Film from Philosophy of the West and Islam) 3. The Significance of Film Criticism in Malaysia for the Industry and Audiences Conclusion Film as Seventh Art; the link between philosophy and film is significant. Film is philosophical argumentative medium. It is argumentative in the sense of knowledge development, the thinking process in studying a film. Recommendation The Seventh Art epigrammatic methodologyl concept, as the theoretical aspects in filmmaking and film studies to be enhanced. Other recommendations cited on the chapter eight.